Effects of Adding Neuromuscular Electrical Stimulation to Traditional Military Amputee Rehabilitation. Issue 1 (1st January 2017) - Talbot, Laura A.; Brede, Emily; Metter, E. Jeffrey
ABSTRACT: Background: Traumatic transtibial amputations lead to an early decline in the use and weight bearing of the residual limb. These changes result in progressive quadriceps muscle atrophy with strength loss that affects standing and walking. Neuromuscular electrical stimulation (NMES) may be useful as an adjunct to amputee prosthetic rehabilitation to maintain quadriceps muscle strength and mass. The objective of this pilot study was to compare the effects of a home-based NMES rehabilitation program plus the traditional military amputee rehabilitation program (TMARP) to the effects of TMARP alone on quadriceps muscle strength, functional mobility, and pain in military service members after a combat-related lower extremity amputation. Methods: In total, 44 participants, aged 19 to 46 years, with a unilateral transtibial amputation were randomly assigned to the TMARP plus NMES ( n = 23) or to TMARP alone ( n = 21). Both groups received 12 weeks of the traditional amputee rehabilitation, including pre- and postprosthetic training. Those in the NMES group also received 12 weeks of NMES, 15 to 20 minutes/day, 5 days a week. Participants were tested at 3-week intervals during the study (baseline, 3, 6, 9, and 12 weeks) for muscle strength and pain. For functional measures, they were tested after receiving their prosthesis and at study completion (weeks 6 and 12). Results: In both groups, residual limb quadriceps muscle strength and pain severity improved from baseline to 12 weeks. The NMES plus TMARP group showed greater strength than the TMARP alone group at 3 weeks, before receiving the prosthesis. However, 6 weeks after receiving their prosthesis, there was no group difference in the residual limb strength. Functional mobility improved in both groups between weeks 6 and 12 with no difference between the two treatment groups. Discussion: A home-based NMES intervention with TMARP worked at improving residual limb strength, pain, and mobility. NMES seemed most effective in minimizing strength loss in the amputated leg before receiving the prosthesis. Further research on amputation rehabilitation is warranted as NMES may accelerate recovery post amputation.